A new species of the genus Tshurtshurnella Kusnezov, 1927 (Hemiptera: Fulgoromorpha: Issidae) from Turkey - Tanyeri̇, Ruki̇ye; Zeybekoğlu, Ünal (Zootaxa, 2020)
Tshurtshurnella sinopei sp. nov. is described after the specimens collected in Sinop, Western Black Sea Region of Turkey, in August 2017. External morphology including male and female genital structures of the new species are described and illustrated.